THE WITNESS’S RIGHT AGAINST SELF-INCRIMINATION. NATIONAL STANDARD - Ioan-Paul CHIȘ (Challenges of the Knowledge Society)
This study is meant to reveal the legal solution in the Romanian system regarding the witness’s right not to contribute to self-incrimination. Thus, as a translation of the principle nemo testis idoneus in re sua, the Romanian legislator stipulated the witness’s right against self-incrimination under the privilege of not using his statements, in consideration of his locus standi, against him, regardless of the fact that he later on was given the status of a defendant for the same offence or whether he is a defendant in a different case, which is connected to the one where he is a witness. Likewise, the privilege of not using his statements against him, stipulated under these conditions in the criminal procedure law, seems to respond to the three difficult choices that the witness has, a premises for the necessity to formulate, on a jurisprudential bases, the witness’s right to remain silent and the right against self-incrimination.